PERANCANGAN ARSITEKTUR SISTEM FINGERPRINT MENGGUNAKAN TOGAF PADA PT RODA PRIMA PERKASA - Dheren Harliana Halim; Nicholas Nicholas; Darren Hansen; Lionnell Julycell Huang; Wilbert Anderson; Dicky Pratama (Jurnal Riset Sistem Informasi, 2026)
PT Roda Prima Perkasa has implemented a fingerprint-based attendance system; however, attendance data management remains suboptimal due to limited integration and manual recapitulation processes. This study aims to design a structured and integrated fingerprint attendance system architecture using The Open Group Architecture Framework (TOGAF). Data were collected through interviews, observations, and documentation studies of the existing system. The research methodology follows the stages of the TOGAF Architecture Development Method (ADM), including the Preliminary Phase, Architecture Vision, Business Architecture, Information Systems Architecture, and Technology Architecture. The results consist of a proposed fingerprint attendance system architecture covering business, application, data, and technology aspects, with centralized data management and the use of an Attendance Management System to support more effective attendance processing.